2014
DOI: 10.1007/s11605-013-2388-x
|View full text |Cite
|
Sign up to set email alerts
|

Clinical and Pathologic Features Influencing Survival in Patients Undergoing Pancreaticoduodenectomy for Pancreatic Adenocarcinoma

Abstract: The strongest prognostic variable for short- and long-term survival after PD for PDA is lymph node ratio. Short-term survival is influenced by the postoperative course.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
14
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 24 publications
(15 citation statements)
references
References 25 publications
1
14
0
Order By: Relevance
“…Complete resection is the most effective modality for improving the survival of PDAC patients, with an estimated 5-year survival rate of 4–25% [2]. Due to the anatomical proximity, direct tumor infiltration of the superior mesenteric vein (SMV)/portal vein (PV) is not uncommon in PDAC.…”
Section: Introductionmentioning
confidence: 99%
“…Complete resection is the most effective modality for improving the survival of PDAC patients, with an estimated 5-year survival rate of 4–25% [2]. Due to the anatomical proximity, direct tumor infiltration of the superior mesenteric vein (SMV)/portal vein (PV) is not uncommon in PDAC.…”
Section: Introductionmentioning
confidence: 99%
“…More specifically, the CART analyses suggest that the two most important risk factors for determining 1-year mortality were the LNR and tumor size, while only the LNR was able to risk-stratify patients at 3 years. A focused, separate analysis of 246 patients with specifically pancreatic adenocarcinoma reported a significant prognostic value of the LNR for both short- and long-term survival after PD [25]. This was similarly confirmed in a recent study of 551 patients who underwent resection for periampullary tumors, and a LNR > 0.2 was identified as an independent prognostic factor for overall survival [28].…”
Section: Discussionmentioning
confidence: 72%
“…In contrast, retrospective evaluations of pancreatic cancer and ampullary carcinoma demonstrated that the number of metastatic nodes, but not LNR, was one of the most important prognostic factors [21, 22]. However, a significant association between the LNR and survival for patients with pancreatic cancer was identified in separate studies [6, 2325]. Furthermore, using data from patients undergoing pancreaticoduodenectomy for pancreatic adenocarcinoma, the LNR has been shown to be one of the most powerful predictors of short- and long-term survival [25] and has been suggested as a new tool for stratifying patients in future trials [6].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…This staging system remains the primary consideration by physicians to determine appropriate treatment as well as offer prognostic information for patients and families [3]. Significant ranges in survival exist within individual AJCC clinical stages [4], [5], [6]; for instance, stage IV patients may live only a few weeks after diagnosis or may live longer than one to two years with treatment. It is likely that this intra-stage variance is due to heterogeneous tumor gene expression resulting in differences in tumor biology.…”
Section: Introductionmentioning
confidence: 99%